(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
A ratio of category of "obligation" with categories of "legal relationship", "duty" and "contract" is analyzed in the article. The problem of the broad understanding of the obligation leading to use of norms on obligations not to aims, not effectively, causing miscarriages of justice is discussed. The author makes an attempt to understand the nature of obligations and their difference from other civil legal relationship.